(untitled) (Lead City International Journal of Library, Information & Communication Sciences, 2024)
The importance of quality service delivery in research institutes’ libraries cannot be overemphasized as it determines the quality of information services delivered in these libraries and the research productivity of the users. Literatures have established that an institution factor is one of the important factors that determine quality of service delivery in research institute library. This study examines the quality of service delivery and also determines the influence of institution factors on quality service delivery in research institute south-West, Nigeria.The study adopted survey research design. The population comprised 140 library personnel from 27 research institutes in South-West, Nigeria. A structured and validated questionnaire was used to collect data. The result shows a positive quality service delivery (mean= 2.77) in research institute libraries and institutional factors has a significant influence on quality service delivery (?=.255, P< 0.05).The study concluded that institutional factors play important roles in ensuring effective quality service delivery in research institutes’ libraries in South-West, Nigeria. The study recommended that parent organisations of research institutes should give more support to improve the institutional factors prevailing in their libraries.